The Role of Controlling Inflation in the Perspective of Al-Qur'an - Kuni Zakiyah (Universitas Airlangga, 2018)
The phenomenon of inflation that exists is actually not a short-term phenomenon and occurs situationally. However, like in other developing countries, the problem of inflation is more on the issue of long-term inflation that is increasingly complex and increasingly difficult to control. Conventional economic policies are no longer able to solve this problem. According to the perspective of the Qur'an, the source of the emergence of economic turmoil, which is indicated by high inflation, is due to the use of currencies that deviate from the Qur'an. The deviation is nothing but making the currency a commodity in order to make a profit. The advantage is called by the Qur'an in terms of usury, both usury nasi’ah and fadhl. Therefore, if we want to create a more stable economy, with a more controlled inflation rate, then there must be courage to eliminate the source of the main cause.